2018
DOI: 10.1111/febs.14378
|View full text |Cite
|
Sign up to set email alerts
|

PKA‐binding domain of AKAP8 is essential for direct interaction with DPY30 protein

Abstract: The main function of the A kinase-anchoring proteins (AKAPs) is to target the cyclic AMP-dependent protein kinase A (PKA) to its cellular substrates through the interaction with its regulatory subunits. Besides anchoring of PKA, AKAP8 participates in regulating the histone H3 lysine 4 (H3K4) histone methyltransferase (HMT) complexes. It is also involved in DNA replication, apoptosis, transcriptional silencing of rRNA genes, alternative splicing, and chromatin condensation during mitosis. In this study, we focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…To date, very few of the aberrantly spliced isoforms identified in SFmut malignancies have been functionally characterized. 6 We identified aberrant splicing of the mitosis regulators SEPT2 99,100 and AKAP8, 71 leading to their downregulation in the CD34 1 cells of SF3B1mut and SRSF2mut MDS, respectively. Anemia is a hallmark of MDS, 1 and we found that knockdown of SEPT2 or AKAP8 in human hematopoietic progenitors resulted in markedly impaired erythroid cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, very few of the aberrantly spliced isoforms identified in SFmut malignancies have been functionally characterized. 6 We identified aberrant splicing of the mitosis regulators SEPT2 99,100 and AKAP8, 71 leading to their downregulation in the CD34 1 cells of SF3B1mut and SRSF2mut MDS, respectively. Anemia is a hallmark of MDS, 1 and we found that knockdown of SEPT2 or AKAP8 in human hematopoietic progenitors resulted in markedly impaired erythroid cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…AKAP8 and SEPT2 play important roles in the regulation of mitosis and cell growth. 70,71 Cell growth is dysregulated in MDS, [1][2][3][4] and thus we selected AKAP8 and SEPT2 for functional studies.…”
Section: Functional Effects Of Splicing Aberrations Associated With Smentioning
confidence: 99%
“…The PKA scaffold Akap8, which binds to Ambra1 in the nucleus, has itself previously been strongly linked to histone modifications and chromatin changes. Indeed, by interacting with the MLL1/ MLL complex via Dpy30, Akap8 regulates histone H3K4 methyltransferase complexes and binds to the nuclear matrix, nucleoporin component Tpr, as well as chromatin; in turn, this contributes to chromosome condensation and transcription, effects that are important for the mitotic checkpoint (41,(48)(49)(50)(51). Akap8 also binds the histone deacetylase HDAC3 and influences mitosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…S2). In addition, Akap8 has been reported to bind to Dpy30, a core subunit of H3K4 histone methyltransferases (41). Therefore, we next addressed whether Ambra1 and Akap8 influence histone modifications by transfecting SCC FAK-WT and 2/2 cells with siControl, siAmbra1 (Fig.…”
Section: Ambra1 and Akap8 Regulate Histone Modificationsmentioning
confidence: 99%
“…This experiment was performed as previously described 63 min. Subsequently, the reactions were spotted on P81 membrane (Whatman), which were then air-dried, washed 3 times with 50 mM carbonate buffer pH 9.2, rinsed in acetone and after soaking in scintillation cocktail used to count 3 H signal.…”
Section: Far Western Blottingmentioning
confidence: 99%